(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
Plant population has a strong influence on rice yield. A field experiment was conducted during the 2017 and 2018 main cropping seasons at Guraferda district in Bench Sheko Zone, Southwest Ethiopia. The objective of this study was to determine the optimum plant population and appropriate variety on grain yield and yield components of upland rice. The experiment was carried out using RCBD with three replications. Five levels of plant populations (60, 80, 100, 120, and 140 kg ha-1) and three levels of genotypes (Nerica-4, Suparica-1, and Local check) were studied. The main effect of plant population and variety had significant (p<0.05) for most of the parameters investigated. However, the interaction effect had only statistically significant for the number of tillers, panicles, and grain yield. The combined results showed that the maximum grain yield of 5553.3, 5491.0, 5252.5, 5047.6, 5043.1, and 4955.6 kg ha-1 were obtained at the respective treatment combinations of Suparica-1 with 80, Suparica-1 with 100, Local check with 140, Suparica-1 with 120, and Local check with 120 and 100 kg ha-1 plant populations. In addition to the above result, a Partial budget analysis was also carried out to determine the economic optimum plant population for production. Accordingly, the combination of Suparica-1 at the rate of 80 kg ha-1 was appropriate to get a better yield and higher economic benefit. Therefore, it can be possible to suggest the finding for wider production. Int. J. Agril. Res. Innov. Tech. 12(1): 94-100, June 2022